2019
DOI: 10.5435/jaaos-d-17-00758
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Limb Salvage Versus Amputation for Nonmetastatic Sarcomas Using Patient-reported Outcomes Measurement Information System Outcomes

Abstract: Introduction: The Patient-reported Outcomes Measurement Information System (PROMIS) is a scoring tool that allows comparisons between patients with rare conditions and more common ailments, or the general US population. PROMIS outcomes were compared between the limb salvage and amputee patients for nonmetastatic sarcomas to the US population. Methods: One hundred thirty-eight patients were included in the analysis. Patients were divided into the limb sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…The current study seems consistent, as it found no difference in PROMIS outcomes in patients undergoing pre- versus post-operative RT at later timepoints of median 52 and 72 days, respectively. Indeed, multiple studies have shown functional recovery in patients following STS resection that continues for up to two years after an initial decline [32] , [33] , [34] , [35] .…”
Section: Discussionmentioning
confidence: 99%
“…The current study seems consistent, as it found no difference in PROMIS outcomes in patients undergoing pre- versus post-operative RT at later timepoints of median 52 and 72 days, respectively. Indeed, multiple studies have shown functional recovery in patients following STS resection that continues for up to two years after an initial decline [32] , [33] , [34] , [35] .…”
Section: Discussionmentioning
confidence: 99%
“…All of this occurs in the setting of a comprehensive cancer center where a close relationship exists between medical, radiation, and surgical oncologists who work together to address cancer-specific considerations in the oncologic amputee population.In our study, TMR reduced patient-reported phantom and residual limb pain behavior and interference compared to unselected general oncologic amputee controls beyond the clinically meaningful threshold for this population. Raw PROMIS pain interference scores in our study population undergoing amputation with concurrent TMR for oncologic diagnoses demonstrated favorable outcomes in comparison to both oncologic amputees and limb salvage patients in the recent study by Wilke et al89 In a population with similar follow-up, they demonstrated PROMIS pain interference scores of 53.8 and 53.3 for limb salvage and amputation respectively. These are both higher (more pain interference) than our findings of phantom pain related pain interference of 42.1 and 46.2 for >1 year and <1 year follow-up, respectively, and residual limb pain related pain interference of 44.0 and 44.1 for >1 year and <1 year follow-up, respectively, after TMR.…”
mentioning
confidence: 94%
“…There are some studies including only subgroups as soft tissue sarcomas but they ended with small numbers such as 18 [13] or 39 [21]. Even mixed groups of bone and soft tissue sarcomas from recent years reached sometimes only small numbers, such as 24 [22]. If the authors try to focus on location as distal tibia and entity as osteosarcoma, the resulting numbers are as small as 19 amputations even in a large center such as the Rizzoli [12], or 25 patients with soft tissue sarcoma of the extremities at Mount Sinai Hospital, Toronto [23].…”
Section: Discussionmentioning
confidence: 99%